Improved Semidwarf Rice Lines with Tolerance to Submergence of Seedlings - Mackill, D.J.; Amante, M.M.; Vergara, B.S.; Sarkarung, S. (Wiley, 1993)
Short‐term submergence of rainfed lowland and deepwater rice (Oryza sativa L.) reduces yields on millions of hectares in South and Southeast Asia. Farmers in these areas lack high‐yielding cultivars that are tolerant to submergence at the vegetative stage. The present study was conducted to evaluate the submergence tolerance, yields and agronomic characteristics of improved submergence‐tolerant rice lines. Experimental lines combining short to intermediate stature (80–115 cm) with tolerance to submergence were developed from tall, lowyielding tolerant cultivars at the International Rice Research Institute Los Baňos, Philippines. Lines were selected based on high survival after submergence in concrete tanks and visual evaluation of yield potential in the field. These lines were tested in field and glasshouse tanks for survival after 10 to 13 d of submergence and were evaluated in replicated trials in the dry and wet seasons. Experimental lines selected for submergence tolerance from crosses with tolerant parents showed higher survival than lines not selected for tolerance in the field and glasshouse tests. The most tolerant lines showed low yield potential (≤4100 kg ha−1); however, one breeding line with high submergence tolerance (IR49830‐7‐1‐2‐2) yielded 4880 kg ha−1 and was among the highest yielding lines in the trial. This shows that submergence tolerance can be incorporated into improved, high‐yielding lines, which can raise productivity in submergence‐prone areas. Submergence tolerance may also be useful for systems in which rice is seeded directly into standing water, where deep water during crop establishment has been proposed as a means of suppressing weed growth.